Notating Extreme Metal: A Practice-Led Approach - Nachenius, Marco Christian (Stellenbosch : Stellenbosch University, 2021)
ENGLISH ABSTRACT: This dissertation will discuss the composition of Argo, a large-scale musical work in the extreme metal genre that is written primarily for extreme metal performers. Argo is written in a notational framework that is commonplace in 21st century Western Art Music, but very uncommon in extreme metal. This research will show how and why notation is very rarely used in extreme metal for the creation and performance of musical works. Argo is theoretically positioned in the stylistic and idiomatic framework of extreme metal and in the notational framework Western Art Music. This will include a dissemination of the specific elements of Argo that allows for its placement within the extreme metal genre. With regards to notation, this research will show that Argo shares stylistic similarities with twentieth-century indeterminate music, while still primarily relying on standardised notational symbolism from the nineteenth and early twentieth century. It will also be shown how the methodological framework of artistic research can be used as an answer for assimilating my own creative practice in an academic setting for the generation of new knowledge. Through the use of artistic research methodologies, this dissertation critiques the notion of notation, the musical work and the performer/composer roles within popular music broadly, and extreme metal specifically.